Development of a handheld fluorescence imaging device to investigate the characteristics of protoporphyrin IX fluorescence in healthy and diseased skin - Kulyk, Olena; Ibbotson, Sally H.; Moseley, Harry; Valentine, Ronan M.; Samuel, Ifor D.W. (Photodiagnosis and photodynamic therapy, 2015)
[Display omitted] •We developed a handheld device and a time course method for fluorescence imaging.•The device can be used to study PpIX formation in healthy and diseased skin.•PpIX fluorescence grows throughout the 3h prior to treatment.•The fluorescence intensity varies between diagnoses and individuals.•The fluorescence depends on the body site, possibly due to differences in temperature. Topical Photodynamic therapy (PDT) is an effective treatment for superficial non-melanoma skin cancers (NMSC) and dysplasia. During PDT light activates the photosensitiser (PpIX), metabolised from a topical pro-drug. A combination of PpIX, light and molecular oxygen results in inflammation and cell death. However, the outcomes of the treatment could be better. Insufficient biosynthesis of PpIX may be one of the causes of incomplete response or recurrence. Measuring surface fluorescence is usually employed as a means of studying PpIX formation. The aim of this work was to develop a device and a method for convenient fluorescence imaging in clinical settings to gather information on PpIX metabolism in healthy skin and NMSC with a view to improving PDT regimes. A handheld fluorescence camera and a time course imaging method was developed and used in healthy volunteers and patients diagnosed with basal cell carcinoma (BCC) and actinic keratosis (AK). The photosensitiser (precursor) creams used were 5-aminolaevulinic acid (ALA; Ameluz®) and methyl aminolevulinate (MAL; Metvix®). Pain was assessed using a visual analogue score immediately after the PDT. Fluorescence due to PpIX increases over three hours incubation in healthy skin and in lesional BCC and AK. Distribution of PpIX fluorescence varies between the lesion types and between subjects. There was no significant correlation between PpIX fluorescence characteristics and pro-drug, diagnosis or pain experienced. However, there was a clear dependence on body site. The device and the method developed can be used to assess the characteristics of PpIX fluorescence, quantitative analysis and time course. Our findings show that body site influences PpIX fluorescence which we suggest may be due to the difference in skin temperature at different body sites.